DEVIDE ET IMPERA IN JONATHAN SWIFT’S NOVEL GULLIVER’S TRAVELS - Endah Hari Utama; Muhammad Fatih Suhadi (Universitas Islam Sumatera Utara, 2022)
This study discusses Devide et Impera in the novel Gulliver’s Travels, written by Jonathan Swift and published in 1726. This research is motivated by the writers’ interest in knowing about the conflict between the Lilliput and Blefuscu countries. The method used in this research is a descriptive qualitative method, and one of the significant theories used in this research is proposed by Morrock, who claims that there are four major tactics commonly used by those who make use of this Devide et Impera strategy. Seeing the divisions between the two countries, the reason is due to disagreements on how to crack eggs correctly. Emperor Liliput argues that the way to break eggs is with a sharp tip, while Blefuscu’s is different. As a result of these differences of opinion, in the end, it leads to an extraordinary conflict, namely a war that claims lives and weakens the economies of the two countries based on political strategy and political influence.